Exploration the Influence of Ag+ Ion Solution Concentration Variations Coated on Biofoam Based on Cassava Starch and Corn Fiber on Crystallinity, Density, and Porosity - Ginting, Pariaman; Sutiarno, Sutiarno; Wijaya, Galang Haedi; Karo, Pulung Karo; Suka, Ediman Ginting; Riyanto, Agus (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
The bio-foam in this study was made from biopolymers in the form of cassava starch, cellulose from corn stalks, and a binder polymer in the form of polyvinyl alcohol (PVA). The bio-foam was molded using the thermo pressing method at T = 150 °C and pressed for t = 3 minutes. Ag+ ions were added as an initial review of the physics properties of the bio-foam to serve as a reference for future antibacterial bio-foam manufacturing. Ag+ ions were produced using the electrolysis method from AgBr rods with an electric voltage of 15 volts. Then, the electrolyzed solution containing Ag+ ions was varied in concentration (12 ppm, 17 ppm, 22 ppm, 27 ppm). The ions were then coated on the bio-foam using the dip coating method and dried at room temperature. Along with the increase in the concentration of the Ag+ ion solution coated on the bio-foam, there was an increase in the bio-foam crystallinity with test values of 34.4%, 40.8%, 41.2%, and 42.6%, respectively. Based on these data, the crystallinity value of the bio-foam does not change significantly. It also aligns with the density test values, which tend to be constant with an average test value of 0.322 g/cm³. Furthermore, the concentration of the solution containing Ag+ ions did not influence the bio-foam's porosity properties, where the four samples tended to remain with an average value of 5.9%.